Unifiability and Structural Completeness in Relation Algebras and in Products of Modal Logic S5 - Dzik, Wojciech; Wróbel, Beniamin (Bulletin of the Section of Logic, 2015)
Unifiability of terms (and formulas) and structural completeness in the variety of relation algebras RA and in the products of modal logic S5 is investigated. Nonunifiable terms (formulas) which are satisfiable in varieties (in logics) are exhibited. Consequently, RA and products of S5 as well as representable diagonal-free n-dimensional cylindric algebras, RDfn, are almost structurally complete but not structurally complete. In case of S5n a basis for admissible rules and the form of all passive rules are provided.